Cortical thickness and resting‐state cardiac function across the lifespan: A cross‐sectional pooled mega‐analysis. (10th October 2020) - Koenig, Julian; Abler, Birgit; Agartz, Ingrid; Åkerstedt, Torbjörn; Andreassen, Ole A.; Anthony, Mia; Bär, Karl‐Jürgen; Bertsch, Katja; Brown, Rebecca C.; Brunner, Romuald; Carnevali, Luca; Critchley, Hugo D.; et al.
Abstract: Understanding the association between autonomic nervous system [ANS] function and brain morphology across the lifespan provides important insights into neurovisceral mechanisms underlying health and disease. Resting‐state ANS activity, indexed by measures of heart rate [HR] and its variability [HRV] has been associated with brain morphology, particularly cortical thickness [CT]. While findings have been mixed regarding the anatomical distribution and direction of the associations, these inconsistencies may be due to sex and age differences in HR/HRV and CT. Previous studies have been limited by small sample sizes, which impede the assessment of sex differences and aging effects on the association between ANS function and CT. To overcome these limitations, 20 groups worldwide contributed data collected under similar protocols of CT assessment and HR/HRV recording to be pooled in a mega‐analysis ( N  = 1, 218 (50.5% female), mean age 36.7 years (range: 12–87)). Findings suggest a decline in HRV as well as CT with increasing age. CT, particularly in the orbitofrontal cortex, explained additional variance in HRV, beyond the effects of aging. This pattern of results may suggest that the decline in HRV with increasing age is related to a decline in orbitofrontal CT. These effects were independent of sex and specific to HRV; with no significant association between CT and HR. Greater CT across the adult lifespan may be vital for the maintenance of healthy cardiac regulation via the ANS—or greater cardiac vagal activity as indirectly reflected in HRV may slow brain atrophy. Findings reveal an important association between CT and cardiac parasympathetic activity with implications for healthy aging and longevity that should be studied further in longitudinal research. Impact Statement: Understanding which brain areas are associated with autonomic function has important clinical implications. Previous research was limited to small samples. Aiming for a thorough and large replication, we investigated n  = 1, 218 healthy subjects in a pooled mega‐analysis. We found unique associations between vagal activity and cortical thickness of frontal brain areas. It is suggested that greater integrity of prefrontal brain areas may be vital for the maintenance of adaptive autonomic nervous system activity in aging.